2015
DOI: 10.1016/j.jhep.2015.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cell markers predict outcome of patients with hepatocellular carcinoma beyond Milan criteria undergoing liver transplantation

Abstract: HCC patients transplanted beyond Milan criteria without gene signatures of progenitor markers (CK19 and S2) achieved survival rates similar as those within Milan criteria. Once prospectively validated, these markers may support a limited expansion of LT indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 47 publications
(66 reference statements)
5
50
2
Order By: Relevance
“…Therefore, as combination of morphological tumor parameters and serum HCC markers in the selection process is gaining increasing popularity among transplant centers78101316171819, the relevance of obtaining data on the presence of microvascular invasion appears to become far less important for the clinical practice. This observation corresponds to previous findings of other authors regarding no significant impact of microvascular invasion in multivariable analyses including these important features434445.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, as combination of morphological tumor parameters and serum HCC markers in the selection process is gaining increasing popularity among transplant centers78101316171819, the relevance of obtaining data on the presence of microvascular invasion appears to become far less important for the clinical practice. This observation corresponds to previous findings of other authors regarding no significant impact of microvascular invasion in multivariable analyses including these important features434445.…”
Section: Discussionsupporting
confidence: 92%
“…In despite of lacking simple, rigorous assays for defining the number of CSCs [29], measuring CSCs biomarkers potentially help clinicians to relist LT candidates. Llovet JM et al revealed that HCC patients without CSCs markers expression transplanted beyond Milan criteria achieved TFS rates similar as HCC patients transplanted within Milan criteria [30]. We investigated the role of FAM83D in CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although whether RFA can be considered as a competitive alternative to resection is uncertain in early stage HCC, measurement of WFA-sialylated MUC1 may be helpful for selection of those patients suitable for RFA treatment. It has been reported that HCC patients transplanted beyond the Milan criteria without histochemical HPC feature achieved good survival, similar to those within the Milan criteria 13 . Therefore, WFA-sialylated MUC1 may support a limited expansion of liver transplantation indications.…”
Section: Discussionmentioning
confidence: 83%
“…Those subtypes of HCCs with HPC/biliary features have been associated with more aggressive biological characteristics, including recurrence and metastasis. Cytokeratin 19 (CK19) is known as a marker of HPC/biliary features and the expression of CK19 in HCC tissue has been linked to a poor prognosis 913 . Furthermore, mucin-1 (MUC1) is also known as a biliary marker in HCC tissues and the expression of MUC1 in HCC is also associated with a poor prognosis 14, 15 .…”
Section: Introductionmentioning
confidence: 99%